2016
DOI: 10.1371/journal.pone.0161605
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Negative Feedback Control: A Natural Approach for the Design of Synthetic Controllers

Abstract: Many of the most important potential applications of Synthetic Biology will require the ability to design and implement high performance feedback control systems that can accurately regulate the dynamics of multiple molecular species within the cell. Here, we argue that the use of design strategies based on combining ultrasensitive response dynamics with negative feedback represents a natural approach to this problem that fully exploits the strongly nonlinear nature of cellular information processing. We propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 54 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…Adaptation is an important emergent property of engineered feedback control systems and components of the immune system operating inside and out of the CNS (Brudecki et al, 2013 ; Anderson et al, 2015 ; Montefusco et al, 2016 ). Our previous study showed that IL-10 restrained the adaptation of the TNFα response to LPS in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Adaptation is an important emergent property of engineered feedback control systems and components of the immune system operating inside and out of the CNS (Brudecki et al, 2013 ; Anderson et al, 2015 ; Montefusco et al, 2016 ). Our previous study showed that IL-10 restrained the adaptation of the TNFα response to LPS in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…High-gain negative feedback is known to improve the reliability of systems that are uncertain: operational amplifiers are a classical example that illustrate how the output of a high-gain device can precisely track the input, despite uncertainty in the gain, as long as negative feedback is present. Potential disadvantages of high-gain controllers include instability (which in our case could introduce oscillations), and chattering, a phenomenon where the controller rapidly switches between its on and off states and often occurs in sliding mode controllers [78]. Instability can be prevented by imposing suitable limitations on the closed-loop gain; if the process gain is fixed, this gain reduction would fall on the controller and possibly reduce its ultrasensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Allosteric binding of proteins, which is known to be ultrasensitive, can be used to generate logarithmic sensors [79]. The yeast osmoregulation system combines ultrasensitivity of the MAPK pathway with negative feedback to achieve perfect adaptation [80,81,78]. Adaptation has also been observed in ultrasensitive enzymatic networks examined using in silico evolutionary algorithms [82].…”
Section: Discussionmentioning
confidence: 99%
“…This was true of not only the convergence rate on the coagulation problem, but also the biochemical benchmark problems; DOPS required two-orders of magnitude fewer function evaluations compared with enhanced Scatter Search (eSS) to estimate the biochemical benchmark model parameters. What remains to be explored is the performance of DOPS compared to techniques that utilize derivative information, either on their own or in combination with other meta-heuristics, and the performance of DOPS in real-world applications compared with other meta-heuristics such as hybrid genetic algorithms e.g., see [ 52 ]. Gradient methods perform well on smooth convex problems which have either a closed form of the gradient of the function being minimized, or a form that can be inexpensively estimated numerically.…”
Section: Discussionmentioning
confidence: 99%